FORM OF LEGAL PROTECTION OF SMALL BUSINESS IN THE CONTEXT OF BUSINESS COMPETITION IN INDONESIA: BENTUK PERLINDUNGAN HUKUM TERHADAP USAHA KECIL DALAM KONTEKS PERSAINGAN USAHA DI INDONESIA - Andreas Prayuda Aprindo (SOSIOEDUKASI, 2023)
This study aims to determine how small businesses in Indonesia are afforded legal protection in the context of business competitiveness. This is normative legal study, which is often referred to as doctrinal legal research. This study employs 2 (two) approaches: the statutory approach and the conceptual method. The findings indicate that the legal protection of small business actors in business competition in Indonesia is a manifestation of the implementation of economic democracy that contains the principles of justice, unity, and fairness to encourage the creation of business opportunities for every citizen in an atmosphere of healthy and reasonable competition so as not to cause the concentration of economic power on only a few business actors, but to provide opportunities for small business actors.